Nutrition and cardiovascular disease: an Asia Pacific perspective - Khor, Geok Lin (HEC Press, 1997)
Changes in the dietary intake patterns of countries in the Asia Pacific region are considered in relation to trends of cardiovascular disease mortality. Cardiovascular disease now constitutes the major cause of mortality in many of the countries of the region. The mortality rate for coronary heart disease (CHD) has been on the decline since the mid-1960s in countries such as Australia, New Zealand and Japan, while a decline in other countries, including Singapore and Hong Kong, appears to be occurring about two decades later after a delayed increase. In contrast, countries like Malaysia and China have had and continue an upward trend for CHD mortality. Nonetheless, the mortality rates due to CHD in New Zealand, Australia, Singapore followed by Hong Kong rank among the highest in the region. In China, Taiwan and Japan, death due to cerebrovascular disease remains a major cause of death, although the latter two countries have undergone a significant decline in stroke death rates since 1970. The intakes of fat from land animal products, fish and vegetable oils, depending on fatty acid patterns and, possibly other constituents, are candidate contributors to the different atherogenic and thrombotic effects. Countries which have a higher mortality from CHD tend to have a higher intake of energy from fat and proportion of fat from animal products. These fat intakes may operate to increase hypercholesterolemia and overweight in various countries. Again, intakes of other food items and constituents used in the region such as soybeans, dietary antioxidants in fruits, vegetables, seeds, cereals, nuts and tea and alcohol consumption are candidate cardioprotectants. The wide dietary scope of Asia Pacific populations, from diverse socio-cultural backgrounds, and at different levels of economic and technological development poses several analytic challenges and opportunities. Future research should improve the datasets and think laterally about pathogenesis and intervention.